The rhyton from Danilo : structure and symbolism of a middle Neolithic cult-vessel - Rak, Omer (Oxbow Books, 2011)
"The so called rhyton from Danilo, an archaeological site near the coastal town of Sibenik in Dalmatia, Croatia, is a four-legged Neolithic vessel made of fired clay that according to the consensus of archaeological opinion was most likely a cult vessel used in rituals of unknown origin and content. "Danilo Culture" is the eponymous name bestowed on a culture flourishing in the period from about 5500-4500 BC at Danilo and at some neighbouring sites. This culture had great influence along the eastern Adriatic coast and its hinterland and produced a significant number of these vessels. Rhyta, which other Neolithic cultures also made, were dispersed throughout a vast area of southeast Europe, from Greece to the Alps. This book is an in-depth study of that mysterious, prehistoric archaeological artifact which, due to its antiquity, structure and symbolism, has become a kind of universal proto-matrix for all relevant mythological and spiritual structures of the Mediterranean zone of later, historic times."--JSTOR website (viewed April 10, 2017).